An Investigation on the extent of usage and challenges faced by tourism SMEs concerning e-marketing: empowering co-creation of value - Mgoduka, Siyasanga; Kaseeram, Irrshad; Heeralal, Shalen (Penerbit Universiti Kebangsaan Malaysia, 2024)
Due to advancements in technology and digital connectivity, travel patterns have changed. Technological developments have increased the amount of information and inspiration available to consumers, and big data analytics allows for the creation of innovative insights. When it comes to implementing cutting-edge technologies, small businesses typically lag behind larger ones. In light of the above, this study aims to examine the extent of usage and challenges SMEs face concerning e-marketing. SMEs in the tourism sector have demonstrated that they are drivers of economic growth through the development of entrepreneurial skills and job creation. In this study, data was qualitatively collected from 14 SME service providers, through a purposive sampling method. The findings revealed that SMEs struggle with the adoption of e-marketing. Moreover, the findings revealed that SMEs are also faced with the challenge of easy access to funding, this was found to affect their flexibility towards digital transformation. Lastly, this study found that SMEs are faced with the challenge of lack of expertise to implement digital transformations. This study concludes that, although in South Africa government funding provided to SMEs through grants plays a critical role, it is still not enough. The government can further their SME development initiatives through public sector and private sector partnerships. By increasing SMEs access to funding, joint SME development programs offer a substantial chance to promote entrepreneurship in South Africa.